Answer:
False
Step-by-step explanation:
an inequality is a relation which makes a non-equal comparison between two numbers or other mathematical expressions.
Answer:
Multiply each equation by the value that makes the coefficients of
x
opposite.
(
−
3
)
⋅
(
2
x
+
5
y
)
=
(
−
3
)
(
20
)
(
2
)
⋅
(
3
x
−
10
y
)
=
(
2
)
(
37
)
Step-by-step explanation:
IT IS C BECAUSE IT IS SAYING IT WAS 43 AND IS NOW DROPPING BY -3
Answer:
0.01
can I have brainliest please
Step-by-step explanation:
X-3y=18
X always has a 1 in front of it so
1x-3y=18
-1x -1x You will have to get -3y by its self.
-3y=-1x + 18 when you move 1x over the = it turns into a -1x
/-3 /-3 /-3 divided everything by -3 to get y by its self
Y= 1/3 - 6 and that is you answer